Tea polyphenols incorporated into alginate-based edible coating for quality maintenance of Chinese winter jujube under ambient temperature. (July 2016) - Zhang, Lihua; Li, Shunfeng; Dong, Yu; Zhi, Huanhuan; Zong, Wei
Abstract: The effects of different concentrations (1 g/L, 3 g/L and 5 g/L) of tea polyphenols incorporated into alginate-based (sodium alginate 1 g/L, glycerol 11.6 g/L and sunflower oil 0.25 g/L) edible coating on the respiration intensity, physicochemical properties, and activities of antioxidant enzymes of fresh winter jujube during 8 days storage under ambient temperature were evaluated. Coated jujube without tea polyphenols and uncoated jujube were stored under the same conditions and served as the controls. The alginate-based edible coating with 1 g/L tea polyphenols significantly reduced red indices, total chlorophylls content, respiration rate, electrolyte leakage and malonaldehyde content while maintaining the ascorbic acid content, total phenol content and the activities of antioxidant enzymes. However, the alginate-based edible coating incorporated with tea polyphenols, whichever their concentrations, had no significant effect on firmness. Alginate-based edible coating with 1 g/L tea polyphenols has a potential to maintain the quality of fresh jujube under ambient temperature. Highlights: Edible coatings were used for jujube preservation under ambient temperature. 1 g/L tea polyphenols incorporated in edible coating was better formulation. The increase of red index, respiration rate, electrolyte leakage and malonaldehyde was restrained. The decline of total chlorophylls content, ascorbic acid and total phenol content was delayed. Activities of antioxidant enzymes were maintained at high level.